Karyological studies in dogs* - Jayashree, R; Thangaraju, P; Nainar, A Mahalinga; Krishnan, A R (The Indian Journal of Animal Sciences, 2012)
The diploid chromosome number in common dog (Canis familiaris) was 2n=78 comprising 76 autosomes and 2 sex chromosomes. All autosomes were acrocentric, the X-chromosome was submetacentric and Y-chromosome metacentric. Three mitogens were tried for leukocyte culture techniques. The mean mitotic drive were 61.30 ± 2.54, 61.25 ± 1.49 and 58.00± 1.91% for PHA, PWM and concanavalin-A, respectively, and their corresponding mitotic indices were 1.66±0.45, 1.00 ± 0.30 and 0.92 ± 0.26%.